Intense biological phosphate uptake onto particles in subeuphotic continental margin waters. Issue 6 (22nd March 2017) - Sokoll, S.; Ferdelman, T. G.; Holtappels, M.; Goldhammer, T.; Littmann, S.; Iversen, M. H.; Kuypers, M. M. M.
Abstract: Elucidating the processes that affect particulate phosphorus (P) export from the euphotic zone and burial in sediments is important for models of global phosphorus, nitrogen, and carbon cycling. We investigated dissolved inorganic Pi incorporation into particles (>0.2 µm) in the subeuphotic zone and benthic boundary layer of high‐productivity Mauritanian and Namibian shelf waters, using 33 PO4 3− tracer experiments combined with a sequential chemical extraction analysis. Pi uptake (5.4 to 19.9 nmol P L −1  d −1 ) by particulate matter was biologically mediated (~50% into the organic fraction) and similar to estimated rates of heterotrophic growth. Thus, a substantial fraction of Pi must be recycled through a particle‐associated microbial pool. Rapid adsorption of 33 P in the anoxic waters of Namibia indicated the additional existence of a large pool of surface exchangeable P. Particle‐associated Pi recycling and adsorption may influence the export flux and ultimate fate of particle bound P in continental shelf waters. Key Points: Rapid uptake of inorganic P into particles in subeuphotic waters of upwelling regions Uptake of P into particles is microbially mediated Redistribution of P within sinking and suspended particles has implications for P sequestration